Age estimates of chokka squid Loligo reynaudii off South Africa and their use to test the effectiveness of a closed season for conserving this resource. Issue 4 (1st October 2020) - Lipiński, MR; Mwanangombe, CH; Durholtz, D; Yemane, D; Githaiga-Mwicigi, J; Sauer, WHH
Abstract : This study presents age distributions in an exploited population of spawning chokka squid Loligo reynaudii together with their back-calculated spawning times, and considers the results in relation to the exploitation of this species. Samples were collected during two closed fishing seasons, in 2003 and 2004. Age after hatching ranged, in males, from 168 to 484 days, with a mean of 323 days (71–425 mm mantle length [ML]), and in females from 125 to 478 days, with a mean of 316 days (83–263 mm ML). Detailed analysis of catches during nine days of fishing after the end of the closed season indicated strongly that the closed season (October–November) has been beneficial for both the chokka resource and the fishery. The temporal distribution of egg-laying events for parental populations, and a high abundance of squid in the days immediately after the end of the closed season, indicate a link between the parental spawning stock and the resulting spawning stock. This hypothesis was formulated using the distribution of egg-laying events in time, the strength of egg-laying events, and data for the daily catch immediately (i.e. nine days) after the closed season. However, the hypothesis requires rigorous testing using statoliths collected over a longer period.